Connecting texture development to die design in extruded flat products - Esterl, Fabian; Nienaber, Maria; Bohlen, Jan; Ben Khalifa, Noomane (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This study investigates the local texture modification of two magnesium alloys (AZ31 and ZX10) and an aluminum alloy (AA6082) based on changes in the die design. For this purpose, a conventional flat die and a modified die, which has been additively manufactured to allow for a significant modification of the material flow, are investigated. Extrusion tests are carried out, followed by a comprehensive examination of the microstructure and local texture development. These experimental results are complemented by finite element analysis of the state variable distribution in the cross section of the extruded band. The results demonstrate that the texture change is connected to the strain path and can therefore be controlled based on the die design. This equally applies to all of the investigated alloys, despite their differences in crystallographic deformation and recrystallization behavior. Accordingly, a rotation of the dominant texture components about ND at the edge of the band of approximately 40°, 45°, and 20° is observed for AZ31, ZX10, and AA6082, respectively. These findings correlate well with the difference in rotation around ND between the dies of 39°, which is calculated numerically based on the deformation gradient tensor. Furthermore, AZ31 and ZX10 demonstrate a broadening of the basal planes in the TD when extruded with the modified die, which can be related to the increased shear strains in the ED/TD plane over the entire width of the band. For ZX10 specifically, a completely different texture is generated due to the combination of the broadened basal planes in TD, the rotation of the dominant texture component around ND, and its tilt in ED, characteristic of extruded Ca-containing Mg-alloys. The investigation on AA6082 further illustrates the importance of the effective temperature and strain rate in the forming zone for its texture development. While no significant change in the microstructure is evident, the increased heat dissipation and smoothed introduction of dislocations during extrusion with the modified die correlates with a transition from Cube to Goss as the dominant texture component.
Keywords: Die Design; Texture Development; Finite Element Analysis; Deformation Gradient Tensor; Basal Plane; Extrusion